Serum 25-hydroxyvitamin D is associated with body fat percentage and skeletal muscle mass in adults: A cross-sectional study - Meutia Atika Faradilla; Deasyka Yastani; Yohana Yohana; Karina Shasri Anastasya; Nabila Maudy Salma (Science Midwifery, 2026)
Background: Vitamin D is widely recognized for its role in bone and musculoskeletal health, yet accumulating evidence suggests it may also influence body composition through regulatory effects on adipose and skeletal muscle tissues. This study aimed to evaluate the association between serum vitamin D status and body composition parameters in adults. Methods: A cross-sectional study was conducted in 77 adults. Serum 25-hydroxyvitamin D [25(OH)D] concentrations were measured using an enzyme-linked immunosorbent assay (ELISA), while body composition (percent body fat and skeletal muscle mass) was assessed using bioelectrical impedance analysis (BIA). Participants were categorized based on vitamin D status, and group comparisons as well as Pearson correlation analyses were performed. Results: The mean age of participants was 35.8 ± 9.6 years, and 40.2% were men. The prevalence of vitamin D deficiency (<20 ng/mL) was 36%, while 68% of participants had suboptimal vitamin D levels (deficiency or insufficiency). Individuals with vitamin D deficiency showed significantly higher body fat percentage and lower skeletal muscle mass compared with the non-deficient group (p < 0.05). Serum 25(OH)D was moderately inversely correlated with body fat percentage (r = −0.41, p = 0.018) and positively correlated with skeletal muscle mass (r = 0.29, p = 0.012). Conclusion: Lower vitamin D status was associated with increased adiposity and reduced skeletal muscle mass in adults. These findings highlight the potential importance of maintaining adequate vitamin D levels as part of strategies supporting healthier body composition. Longitudinal and interventional studies are needed to clarify causality and clinical implications.